Teaching indicators to unravel the kinetic features of host–guest inclusion complexes. Issue 82 (18th September 2020) - Prabodh, Amrutha; Sinn, Stephan; Grimm, Laura; Miskolczy, Zsombor; Megyesi, Mónika; Biczók, László; Bräse, Stefan; Biedermann, Frank
Abstract : Three new, practically convenient methods are introduced for measuring kinetic parameters of supramolecular host–guest and protein–ligand complexes. Combined with thermodynamic data, this allows for an in-depth of the binding mechanism. Abstract : Both thermodynamic and kinetic insights are needed for a proper analysis of association and dissociation processes of host–guest interactions. However, kinetic descriptions of supramolecular systems are scarce in the literature because suitable experimental protocols are lacking. We introduce here three time-resolved methods that allow for convenient determination of kinetic rate constants of spectroscopically silent or even insoluble guests with the macrocyclic cucurbit[ n ]uril family and human serum albumin (HSA) protein as representative hosts.